STRATEGI PENGEMBANGAN INDUSTRI RUMAH TANGGA KERAJINAN BAMBU DI KINILOW KECAMATAN TOMOHON UTARA KOTA TOMOHON - Dennis Kereh; Noortje Benu; Agnes Loho (Universitas Sam Ratulangi, 2017)
ABSTRACTThis study aims to identify internal factors and external factors, and to determine the development strategy of the bamboo handicraft home industry in Kinilow. The study was conducted from March to May 2017. The data used were primary and secondary data. Primary data is obtained through observation and interviews that are divided into two parties: internal party (bamboo handicraft business owner) with 6 (six) respondents who produce and sell bamboo handicrafts, and external parties (local government and consumers). Whereas, secondary data obtained from literature study. Data analysis used is by using SWOT analysis.The results showed that the internal factors include: Raw materials are easy to obtain, relatively cheap raw material prices, good raw material quality, highly skilled manpower, have followed skills training activities, personal capital use, fast production process, difficulty level Low cost, long-lasting product, affordable selling price, not yet have financial record, not yet relationship with financial institution, traditional production equipment, not yet product promotion method through media (online / print), absence of machine use in Production process (technology), No motorized parking space, and Product display is not good. While external factors include: Increased demand from overseas buyers with TIFF event in Tomohon city, Increased demand from local people, Opportunity for exhibition, Potential and market opportunity is wide, Lack of interest of young generation to work in continuing and maintaining bamboo handicraft business, The existence of new competitor in SULUT, the high of substitution with plastic raw material, unsafe business place from landslide disaster, The existence of discourse from government to relocate place.Based on the SWOT diagram, the chosen strategy is a combination of SO strategies: 1) Developing bamboo handicraft products in Kinilow by innovating to create or produce new bamboo handicraft products, 2) Cooperate with the government to keep expanding Network marketing or marketing area.Keywords : Household Industry, Bamboo Handicraft, SWOT.